Nacho Libre - Hess, Jared; Hess, Jerusha (Paramount Pictures; distributed in the Philippines by MagnaVision, 2006)
Ignacio 'Nacho' is a cook by day in a Mexican orphanage who moonlights as a lucha libre wrestler to raise money for the orphans